ESTIMATION AND OPTIMIZATION OF THE VOLUMES OF THE INCREASE TO PRODUCT AND RENDERED SERVICES IN PROGRESS SMALL ENTERPRISE - I. T. Kurbanova; I. C. Gadzhiev (Вестник Дагестанского государственного технического университета: Технические науки, 2016)
Role and place of the small business are shown in development of the economy of the country. They are offered heuristic methods of the estimation of the increase and optimization volume of production and rendered services in progress small enterprise in sloppy economic ambience.